Anachronistic dystopias : constructive tensions between digital and analog imaging - Mutran, Flavya; Rama, Jander (PORTO ARTE: Revista de Artes Visuais, 2013)
The processes of constructing images that take the intersection as artistic strategy encompass much of the current production in the visual arts. This article discusses the recent productions of Flavya Mutran and Jander Rama, whose practices move between the anachronisms of the processes of analog image production and the dystopian vision related to advances in digital images. The transition of these productions through printmaking, drawing and photography raises questions about the stresses and displacements of the subject in contemporary art, caused by the clash between old and new technologies.